Different properties of SV channels in root vacuoles from near isogenic Al-tolerant and Al-sensitive wheat cultivars - Wherrett, T.; Shabala, S.; Pottosin, I.
Patch-clamp experiments revealed that near isogenic ET8 (Al-tolerant)and ES8 (Al-sensitive)wheat cultivars differed significantly in slow vacuolar channel properties. Under control conditions, whole vacuole currents displayed faster deactivation in ES8. Application of 1.4 lM vacuolar Al3+ caused a 20 mV increase in the activation threshold and slowed activation kinetics in ET8 but not in ES8. Channel density was about 30
Keywords: ALT1; VACUOLE; CALCIUM; ACID SOIL; TRITICUM AESTIVUM